2003
DOI: 10.1183/09031936.03.00087303
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of altered quality of life in patients with sleep-related breathing disorders

Abstract: Determinants of altered quality of life in patients with sleep-related breathing disorders. E. Sforza, J.P. Janssens, T. Rochat, V. Ibanez. #ERS Journals Ltd 2003. ABSTRACT: Recent reports have suggested that altered quality of life and well-being are reported by patients with sleep-related breathing disorders (SRBD). There seems to be no data available in the literature on factors underlying these behavioural consequences. In this study, health-related quality of life (HRQL) scores were examined in SRBD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 26 publications
5
32
1
5
Order By: Relevance
“…Un estudio previo evidenció que los pacientes afectados por un SAHS obtuvieron menor puntuación en todas las subescalas del SF-36 que los sujetos de la población general (Mar et al, 2005). Similares resultados fueron aportados por otros autores que utilizaron el SF-36 (Moore, Bardwell, Ancoli-Israel & Dimsdale, 2001;Sforza et al, 2003). Como se ha comentando previamente, estos resultados podrían indicar las importantes consecuencias del SAHS, a través de la hipoxemia intermitente (ID3), y la pobre calidad de sueño sobre los niveles de somnolencia diurna y del cansancio diurno experimentado por los pacientes con SAHS.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Un estudio previo evidenció que los pacientes afectados por un SAHS obtuvieron menor puntuación en todas las subescalas del SF-36 que los sujetos de la población general (Mar et al, 2005). Similares resultados fueron aportados por otros autores que utilizaron el SF-36 (Moore, Bardwell, Ancoli-Israel & Dimsdale, 2001;Sforza et al, 2003). Como se ha comentando previamente, estos resultados podrían indicar las importantes consecuencias del SAHS, a través de la hipoxemia intermitente (ID3), y la pobre calidad de sueño sobre los niveles de somnolencia diurna y del cansancio diurno experimentado por los pacientes con SAHS.…”
Section: Discussionunclassified
“…Sin embargo, los factores responsables son aún desconocidos, si bien se ha involucrado, entre otros aspectos, a la desestructuración del sueño, la somnolencia diurna, la depresión, la ansiedad y la apatía (Andrews & Oei, 2004;Sforza et al, 2003). Moore et al (2001) encontraron correlaciones significativas entre el tiempo total de sueño y seis dimensiones del Cuestionario de Salud MOS.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A kórkép gyanúját veti fel a hangos, légzésszünetekkel járó horkolás, amelyhez túlzott nappali aluszékonyság társul, de gondolnunk kell erre a betegségre terápiarezisztens hypertonia, szívelégtelenség, szívritmuszavarok, diabetes, stroke, depresszió vagy kognitív diszfunkció, gastrooesophagealis refluxbetegség esetén is. Az aluszékony-ság, az apnoéval gyakran együtt járó elhízás és az alvás töredezettsége, a szorongás és a depresszió azok a ténye-zők, amelyek leginkább befolyásolják az életminőség kü-lönböző dimenzióit, és jelentős életminőség-csökkenés-hez vezetnek [7,8].…”
Section: öSszefoglaló Közleményunclassified
“…23 In addition to its detrimental effects on patient health, ES may impinge on activities of daily living. A study by Sforza and colleagues 24 reported that ES contributed more signifi cantly to impairment in all domains of the Medical Outcomes Study Short-Form (36-item) Health Survey (SF-36) than sleep-disordered breathing. ES may also lead to unemployment, relationship issues, reduced social interaction, and poor performance at work, school, or college.…”
Section: Introductionmentioning
confidence: 99%